The Use of Herpes Simplex Virus in Ex Vivo Slice Culture - Friedman, Allyson K. (Curr Protoc Neurosci, 2015)
Herpes simplex virus (HSV) can be used for a wide range of genetic manipulation in ex vivo slices of central nervous system tissue from both young and adult rodents. The fast expression of the HSV viral mediated gene transfer, which can be engineered to produce cell-type specificity, can be utilized in slice cultures for a variety of purposes over a 1-4 day period with spatial and temporal specificity. This protocol exploits the rapid expression of HSV viral vectors by utilizing slice culture for electrophysiological recordings, avoiding the need to do intra-cranial viral injections. Brain slice cultures maintain many aspects of in vivo biology, including functional local synaptic circuitry with preserved brain architecture, while allowing good experimental access and precise control of the extracellular environment, making them ideal platforms for quick access to evaluate expression effects of HSV viral mediated gene transfer on the molecular and cellular properties of specific neurons. This protocol provides an easy way to study neuronal function following expression of these HSV viruses.